Decreasing Racial Bias Through A Facilitated Game and Workshop: The Case of Fair Play. (June 2021) - Pribbenow, Christine Maidl; Caldwell, Kyrie Eleison H.; Dantzler, Donald Dejon; Brown, Percy; Carnes, Molly
Introduction. Fair Play is an avatar-based role-playing video game in which Jamal Davis, a Black graduate student at a research university, navigates implicit forms of racial bias to reach the win-state of earning his PhD and becoming a professor. Fair Play was designed to educate players on the existence of racial bias in science, technology, engineering, mathematics, and medicine (STEMM) fields in an experiential way and to encourage perspective-taking. Research has found that taking the perspective of another can induce empathy, which improves the empathizer's attitudes towards individuals and groups. Paired with a facilitated workshop, Fair Play was also designed to teach bias concepts to increase participants' bias literacy. Intervention. Research on workshops to reduce gender bias suggests that it increased awareness of personal bias, the motivation and self-efficacy to practice bias-reducing strategies, and a more welcoming department climate and the hiring of more women faculty three years after the intervention. Capitalizing on these findings, a 3-hour workshop was developed to reduce race-based bias against Black/African Americans in STEMM using Fair Play. Conclusions. The facilitation of the workshops and Fair Play requires particular competencies due to its topic (racial bias) and player's skepticism about the reality of the bias incidents. Our data suggest that participants who identify as a person of color are more likely to believe that bias exists compared to White players, which can lead to a discussion about how the incidents in the game were designed and scripted. The facilitator also needs to be versed in a number of intentional design choices, such as Jamal not having voiceover and his success. Finally, this paper describes the Facilitator Game, which was developed as a complement to the game and allows a facilitator to jump to bias incidents quickly while debriefing and discussing the game to further participant learning.